WOMAN’S LANGUAGE FEATURES USED BY FEMALE CHARACTERS IN “A STAR IS BORN” MOVIE - Ni Kadek Sindy Arista; Ni Luh Sutjiati Beratha; Ni Wayan Sukarini (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This undergraduate thesis is entitled Woman’s Language features used by the main female character in “A Star is Born” movie. It is aimed to identifying the types of women’s language features and described the context of the situation that influenced women’s language found in the movie. This undergraduate thesis used the documentation method for collecting data. The data was collected from the movie by watching the movie, reading the movie script as well as seen at the subtitle of the movie. Then identify the women’s language features in the dialogue and analyze it using Lakoff’s theory and the theory by Halliday to analyze the context of the situation. In analyzing the data, this undergraduate thesis applied the qualitative paradigm method to present the data, screenshots of the conversation in the movie are used as the data. The result of the analysis shows that not all types of women’s language features are used by Ally in the movie A Star Is Born movie. There were found seven out of ten types of women’s language features. The precise color terms, ‘hypercorrect’ grammar, and empty stress were not found in Ally’s utterances.